Asymmetric heterojunctions between size different 2D flakes intensify the ionic diode behaviour. Issue 37 (19th April 2022) - Ma, He; Jin, Xiaoheng; Du, Yun-Zhe; Dong, Ling-Yu; Hu, Xu; Li, Wen-Cui; Wang, Dongqi; Joshi, Rakesh; Hao, Guang-Ping; Lu, An-Hui
Abstract : Placing 2D building blocks with lateral size differences leads to the formation of an asymmetric heterojunction, which enables evidently ionic current rectification behaviour. Abstract : Here we report on the facile formation of asymmetric heterojunctions between laterally size different 2D flakes, which leads to a prominent gradient in charge distribution at the nanocontact interface and triggers ionic diode-like transport behaviour with a rectification ratio of 110.